APAKAH SUKU BUNGA SBI DAN INFLASI BERDAMPAK TERHADAP KINERJA REKSA DANA SAHAM DI INDONESIA - Aminar Sutra Dewi; Novendra Adri (JURNAL PUNDI, 2022)
The purpose of this study is to analyze the effect of interest rates SBI and Inflation on the performance of Sham Mutual Funds. This research uses Monthly Net Asset Value (NAV) of equity mutual funds registered with the Otoritas Jasa Keuangan (OJK), as well as monthly data on SBI Interest Rates and Inflation obtained from Bank Indonesia monthly report. By using purposive sampling method selected fourteen equity mutual funds that are active and always exist in five years research to analyze as sample. Indicators used in Determining the performance of equity mutual funds is the Sharpe ratio method. Statistical test that used in this research is multiple regression test. Research result shows that the SBI Interest Rate and Inflation have a positive and significant effect on the performance of equity funds.